2019
DOI: 10.1128/aac.02174-18
|View full text |Cite|
|
Sign up to set email alerts
|

Low Antituberculosis Drug Concentrations in HIV-Tuberculosis-Coinfected Adults with Low Body Weight: Is It Time To Update Dosing Guidelines?

Abstract: Antituberculosis drugs display large pharmacokinetic variability, which may be influenced by several factors, including body size, genetic differences, and drug-drug interactions. We set out to determine these factors, quantify their effect, and determine the dose adjustments necessary for optimal drug concentrations. HIVinfected Ugandan adults with pulmonary tuberculosis treated according to international weight-based dosing guidelines underwent pharmacokinetic sampling (1, 2, and 4 h after drug intake) 2, 8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 29 publications
2
47
1
Order By: Relevance
“…Between patient variability was reduced and dosing simplified by adding one FDC tablet for patients under 55 kg ( Figure 1, right panel). Very similar results were obtained when a similar approach was applied to these drugs based on data from Uganda [33]. The results of these studies confirm that higher mg/kg doses are needed in patients in the lower weight bands, and guidelines should be revised to avoid systematic underdosing of low weight patients.…”
Section: Source Of Pharmacokinetic Variability (Section)supporting
confidence: 63%
See 2 more Smart Citations
“…Between patient variability was reduced and dosing simplified by adding one FDC tablet for patients under 55 kg ( Figure 1, right panel). Very similar results were obtained when a similar approach was applied to these drugs based on data from Uganda [33]. The results of these studies confirm that higher mg/kg doses are needed in patients in the lower weight bands, and guidelines should be revised to avoid systematic underdosing of low weight patients.…”
Section: Source Of Pharmacokinetic Variability (Section)supporting
confidence: 63%
“…Similarly, a more recent study from China found that four of five FDCs failed bioequivalence criteria for rifampin [32]. Observational studies in patients have attributed massively compromised bioavailability to product or batch quality [12,14,[33][34][35][36]. Recently, a 20% reduction in the bioavailability of rifampin was described in the 4-drug FDC used in approximately 450 000 South African patients annually [37].…”
Section: Drug Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis did not detect any difference in isoniazid exposure among different ARTs (efavirenz-based, nevirapine-based, lopinavir/ritonavir-based, and atazanavir/ritonavir-based), which contrasts with previous reports. 36,37 However, it may be that our analysis was not powered to detect these differences because 88% of the participants were on efavirenz-based ART.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HIV infection may have reduced serum concentrations of rifampicin, particularly in the setting of severe immunocompromised [5]. Patients who are underweight also have up to 30% reduction in rifampicin exposures, related to malnutrition coupled with low dosing when mg/kg-based dosing algorithms are applied [6,7]. In our opinion, higher rifampicin dosing should routinely be applied in low-weight patients or those with advanced HIV.…”
Section: Rifampicinmentioning
confidence: 98%